Co-pyrolysis of sewage sludge and metal-free/metal-loaded polyvinyl chloride (PVC) microplastics improved biochar properties and reduced environmental risk of heavy metals. (1st June 2022) - Li, Wenjin; Meng, Jun; Zhang, Yule; Haider, Ghulam; Ge, Tida; Zhang, Haibo; Li, Zhangtao; Yu, Yijun; Shan, Shengdao
Abstract: Co-pyrolysis of sewage sludge and plastics have been utilized for producing biochars as a strategy to fix plastic pollution. However, comparative studies on the characteristics and environmental risk of heavy metals in biochars obtained by the co-pyrolysis of sludge and microplastic with/without metal additives are seldom. Here we demonstrated the effects of simulated co-pyrolysis (at 400 °C) of sewage sludge and metal-free or metal-loaded polyvinyl chloride (PVC) microplastics at different mass ratios (1:0, 19:1, 3:1, 1:3, sewage sludge: PVC (w/w)) respectively. Results revealed that co-pyrolysis of metal-loaded PVC and sewage sludge resulted in higher electrical conductivity, ash content, and an acidic pH of biochars as compared to the co-pyrolysis of metal-free PVC and sewage sludge. Addition of metal-loaded PVC increased total concentrations of calcium (Ca), magnesium (Mg), cadmium (Cd), and lead (Pb) in biochars, but reduced the bioavailability of Cd, chromium (Cr), nickel (Ni), and zinc (Zn) in biochars. Analysis of chemical speciation showed that heavy metals (except Pb) in biochars derived from co-pyrolysis of sewage sludge and metal-loaded PVC had higher percentage of more stable fraction (residual fraction) and lower potential ecological risk index ( RI) value. S1AP3 (sludge: metal-loaded PVC = 1:3) biochar had the lowest environmental risk based on RI value (14.41). To sum up the present study suggests that the addition of metal-loaded PVC microplastic in sewage sludge had a positive impact on the immobilization of heavy metals during co-pyrolysis process. Graphical abstract: Image 1 Highlights: Sewage sludge was co-pyrolyzed with metal-free/metal-loaded PVC to produce biochar. Addition of metal-loaded PVC changed the acidic pH of sludge-PVC biochars to alkaline. Addition of metal-loaded PVC increased total Ca, Mg, Cd, and Pb contents in biochars. Addition of metal-loaded PVC reduced biochar bioavailable Cd, Cr, Ni, and Zn contents. Co-pyrolysis of sewage sludge and metal-loaded PVC had a lower ecological risk index.